Analisis Struktur Kepemilikan, Growth Opportunity Terhadap Nilai Perusahaan Dengan Struktur Modal, Margin Laba Dan Kinerja Keuangan Sebagai Variabel Intervening Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Diva Damai Maharani; Hwihanus, Hwihanus (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This research aims to analyze how ownership structure and growth opportunities influence the value of banking companies listed on the Indonesia Stock Exchange by considering capital structure, profit margins and financial performance as intervening variables. This research method uses purposive sampling with a sample size of 5 companies in 2016-2023. This research is expected to provide theoretical contributions in the field of financial management and corporate governance as well as provide practical guidance for banking company management in making strategic decisions to increase company value. The model used in this research was processed using the smart-PLS application. The research results explain that ownership structure has a significant effect on capital structure, while growth opportunity does not have a significant effect on capital structure. Capital structure has a significant effect on profit margins, while financial performance does not have a significant effect on company value. An increase in the number of assets as an illustration of company size and banking companies can consider capital structure management and growth opportunities to improve the quality of financial performance in the future. Apart from that, it provides advice for investors in making the right decisions